2003
DOI: 10.1007/s00439-002-0857-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the CTNNA3 gene encoding human αT-catenin regarding its involvement in dilated cardiomyopathy

Abstract: αT-catenin is a novel member of the α-catenin family, which shows most abundant expression in cardiomyocytes and in peritubular myoid cells of the testis, pointing to a specific function for αT-catenin in particular muscle tissues. Like other α-catenins, αT-catenin provides an indispensable link between the cadherin-based cell-cell adhesion complex and the cytoskeleton, to mediate cell-cell adhesion. By isolating genomic clones, combined with database sequence analysis, we have been able to determine the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The observation that alpha3 and alpha2 share identical exon-exon boundaries [36] suggests to us that alpha3 evolved via a gene duplication of alpha2 coinciding with the origin of amniotes. Unlike alpha1 and alpha2, alpha3 interacts with pkp2 in the area composita (a hybrid adherens junction in the heart muscle), yet co-expresses with alpha1 at intercalated discs of cardiomyocytes [37].…”
Section: Discussionmentioning
confidence: 99%
“…The observation that alpha3 and alpha2 share identical exon-exon boundaries [36] suggests to us that alpha3 evolved via a gene duplication of alpha2 coinciding with the origin of amniotes. Unlike alpha1 and alpha2, alpha3 interacts with pkp2 in the area composita (a hybrid adherens junction in the heart muscle), yet co-expresses with alpha1 at intercalated discs of cardiomyocytes [37].…”
Section: Discussionmentioning
confidence: 99%
“…Mammals possess three isoforms of α-catenin, termed αE-, αN-, and αT-catenin, which originated from the same ancestral gene and share the same location on human chromosome 10 (Janssens et al, 2003). αE-, αN-, and αT-catenin are expressed predominantly, but not exclusively, in epithelia, neurons, and heart/testis, respectively (Herrenknecht et al, 1991; Shapiro and Weis, 2009; Uchida et al, 1994).…”
Section: Functional Analysis Of CCC Evolutionmentioning
confidence: 99%
“…Genome-wide association (GWA) studies screening hundreds of thousands of single-nucleotide polymorphisms (SNPs) simultaneously using microarray systems have proved useful for identifying genetic changes that contribute to complex diseases. CTNNA3 is one of the largest genes in the human genome with 18 exons spanning 2.3 Mbp on chromosome 10q21 (Janssens et al, 2003). Two independent GWA studies identified multiple polymorphisms of CTNNA3 associated with increased susceptibility to toluene diisocyanate-induced asthma in Korean (Kim et al, 2009) and Canadian (Bernstein et al, 2013) workers.…”
Section: αT-catenin Function Outside the Heartmentioning
confidence: 99%